Diencephalic epilepsy in a patient with agenesis of the corpus callosum confirmed by computerised axial tomography. Issue 8 (August 1977) - Carr-Locke, David; Millac, Paul
Abstract : A case of diencephalic epilepsy is described in whom stereotyped attacks of spontaneous hypothermia and diaphoresis occurred over a 20 year period. No abnormality of the hypothalamo-pituitary-adrenal axis was found, and there was no evidence of an intracranial mass lesion. Pneumoencephalography and computerised axial tomography (EMI scan) demonstrated agenesis of the corpus callosum.